PROFIL PSIKOLOGIS PELAKU PEMBUNUHAN BERENCANA: STUDI KASUS DAN IMPLIKASI KRONOLOGIS - Azalia, Anashya; Martha, Putri; Citra, Amelia Kurnia; Permana, Rifka Tria; Antoni, Herli (LPPM, Universitas Muhammadiyah Riau, 2025)
Premeditated murder is a serious form of crime that not only involves acts of physical violence, but also careful planning and complex psychological motives. This research aims to identify and analyze the psychological profile of perpetrators of premeditated murder through a case study approach to several court decisions in Indonesia. Using descriptive qualitative methods, this research examines the perpetrator's life background, psychological condition, thought patterns and motivations that encourage the perpetrator to carry out planned acts of murder. The results showed that most perpetrators showed certain personality traits such as manipulativeness, egocentrism, and low empathy, which in some cases were associated with antisocial or narcissistic personality disorders. In addition, external factors such as economic pressure, relationship conflicts, and past experiences of violence also strengthen the perpetrator's criminal tendencies. These findings have important implications for developing crime prevention strategies, evaluating the risk of recidivism, and formulating more targeted rehabilitation policies. This research also emphasizes the importance of collaboration between criminal justice institutions and forensic psychologists in handling premeditated murder cases comprehensively.